2009
DOI: 10.1007/s00464-009-0741-7
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of baseline cytometry for surveillance of patients with Barrett’s esophagus

Abstract: Cytometry from brush cytology as an add-on to histology appears to be of additional benefit during surveillance of Barrett's esophagus. Whereas an aneuploid/intermediate DICM warrants an early re-endoscopy, a diploid DICM underscores the low-risk status especially of patients with low-grade dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Four studies were population-based (median follow-up, 5.0 years), 2,3,9,21 4 were multicenter studies (median follow-up, 4.7 years), 27,29,39,42 and the remaining were single-center studies (median follow-up, 4.8 years). 19,20,2226,28,3038,40,41 Most studies reported or permitted a missed vs incident cutoff of exactly 12 months to be applied, with the exception of 2 studies reporting cutoffs of 9 and 6 months, 32,39 and 1 study for which only a cutoff of 14 months could be applied. 24 In these 3 studies, EAC (and HGD-EAC) detected before and after their respective cutoffs were classified as missed and incident, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were population-based (median follow-up, 5.0 years), 2,3,9,21 4 were multicenter studies (median follow-up, 4.7 years), 27,29,39,42 and the remaining were single-center studies (median follow-up, 4.8 years). 19,20,2226,28,3038,40,41 Most studies reported or permitted a missed vs incident cutoff of exactly 12 months to be applied, with the exception of 2 studies reporting cutoffs of 9 and 6 months, 32,39 and 1 study for which only a cutoff of 14 months could be applied. 24 In these 3 studies, EAC (and HGD-EAC) detected before and after their respective cutoffs were classified as missed and incident, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…After applying our inclusion and exclusion criteria, the search was narrowed to 90 studies, all of which were reviewed in detail. Ultimately, 10 studies were included for analysis 18,28‐36 . The flowchart of the article search and selection process is outlined in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…There was considerable heterogeneity in the pooled analyses of neoplasia detection rate (I 2 = 97%) and post‐endoscopy Barrett's neoplasia rate (I 2 = 96%). The pooled expanded neoplasia detection rate, based on data available from nine studies, was 14.4% (95% CI: 11.2%‐18.3%, I 2 = 98%) 18,29‐36 …”
Section: Resultsmentioning
confidence: 99%
“…Our search strategy yielded a total 2482 citations, of which 14 citations fulfilled our inclusion criteria for meta‐analysis (Figure ) . Thirteen of these studies cumulatively reported 603 prevalent and incident oesophageal adenocarcinomas in 9657 patients with Barrett’'s (Table ).…”
Section: Resultsmentioning
confidence: 99%